Characterization Of Biofilm Forming Ability Of Staphylococcus Pseudintermedius Isolates - Chitra, M. Ananda; Renjith, R.; Rishvanth , R. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
In this study, biofilm forming capacity of S. pseudintermedius isolates from canine skin infections by quantitative tissue culture plate method was carried out. A total of 53 S.pseudintermedius (SP) isolates were obtained from 90 samples , 24 of them were from pyoderma, 10 from demodicosis and 5 from otitis cases. Fifteen isolates (28%) were confirmed as methicillin resistant S.pseudintermedius (MRSP) by mecA PCR. Prevalence of MRSP in Chennai SP isolates is lower than the western countries. Majority of the SP isolates were either weak (30%) or no ability (34%) to produce biofilm, with only 17% being classified as strong and 19% as moderate biofilm producers. Biofilm formation was not different between isolates of MRSP and MSSP, which correspond to their equivalent virulence clinically. This is the first report of biofilm forming ability of S.pseudintermedius isolates from dogs in India.
Keywords: S.pseudintermedius; skin infections; biofil; dog